Competitive Study of ICICI and HDFC Banks - Trivedi, Bhavana; Khatri, Sakshi N. (SFIMAR Research Review, 2016)
If is said that what you give is what you get This is the basic philosophy of Corporate Social Responsibility. As businesses use the resources of the society; they have a responsibility to reciprocate by doing something beneficial for the society. In a developing nation like India, the banking sector stands at a commanding position in the responsibility of sustainable development through Corporate Social Responsibility. ICICI and HDFC bank have been close competitors and their competition can be seen in their Strategies, activities and operations. Both the banks have contributed towards social issues such as primary health care, skill development, enhancement in livelihood, finance and education. The issue of education has been of a special interest amongst other dimensions. There is still lot of work needed towards development of education in India. This study is to compare and analyze the corporate social responsibility initiatives towards reformation and development of education in India by ICICI and HDFC bank. The study is taken up to provide useful insights to other banks in taking up corporate social responsibility by initiating programs towards development of education and literacy growth in the country and betterment of the society.